Passados imaginados - Marins, Paulo César Garcez (Coleção Museu do Ipiranga 2022, 2022)
In this book, the exhibition "Passados Imaginados", curated by Paulo César Garcez Marins, is the focus of the nine articles written by the Museum's curatorial team, in which the main challenge is to make explicit the subjective representation of the past of these history paintings and monumental sculptures. For the curator, it is essential to assume that these and other images are artifacts inevitably marked by the artists' subjectivities and desires, or by determinations imposed by the commissioners and that should be met by the painters and sculptors during the conception and realization of their works. Museums were and still are powerful spaces in the construction of collective images, and discussing the appropriation of these images is also an objective of the exhibition